STUDI KASUS-KONTROL: FAKTOR RISIKO ADENOMIOSIS PADA WANITA USIA REPRODUKSI DALAM KAITANNYA DENGAN TEKANAN DARAH DAN INDEKS MASSA TUBUH - Gymnastiar, Ashar; Kurniati, Yuni Prastyo (Jurnal Riset Kesehatan, 2025)
Adenomyosis is a benign uterine condition characterized by the presence of endometrial tissue within the myometrium. This study aimed to analyze the association between blood pressure and body mass index with the incidence of adenomyosis. This study employed a case control design, in which the case group comprised patients diagnosed with adenomyosis, while the control group consisted of patients with uterine leiomyoma. The research was conducted at PKU Muhammadiyah Hospital Surakarta. A total of 221 medical record samples were collected using purposive sampling from 2020 to 2024, consisting of 130 cases of adenomyosis and 91 controls of uterine leiomyoma. Clinical variables including blood pressure, body mass index, age, parity, and residence were assessed. Data analysis was performed using Chi-Square tests. The results showed a significant association between blood pressure and the incidence of adenomyosis, with hypertensive women having a 2.7-fold higher risk of adenomyosis compared to normotensive women. In contrast, there was no significant association between body mass index and adenomyosis. In conclusion, the findings suggest that hypertension is a more prominent risk factor than obesity in the development of adenomyosis. Future studies involving to enhance preventive strategies and optimize clinical management.